Strategi Ulama Dayah dalam Memformulasikan Islam Wasathiyah di Aceh - Syafieh, Syafieh; Muammar, Arief (Analisis: Jurnal Studi Keislaman, 2025)
The implementation of Wasathiyah Islam in Aceh faces various challenges, particularly related to the implementation of Islamic law as positive law and the emergence of radical Islamic groups that complicate its implementation and threaten the unity of the ummah and the state. Wasathiyah Islam, as a moderate Islamic teaching that emphasizes balance, is expected to be a solution in reducing radicalization and creating harmony in religious life. This study uses a qualitative approach with a descriptive-analytical method. The data sources used consist of primary and secondary sources, with data analysis techniques that include description, formulation, and interpretation, as well as using thematic analysis techniques. At the end of the study, conclusions were drawn inductively. The results show that Dayah scholars implement several key strategies in formulating Wasathiyah Islam in Aceh, including a moderate approach to religious education and learning, the spread of Islam through da'wah media, interfaith and intercultural dialogue, and the preparation of fatwas supporting moderation. In addition, they also strengthen the values of local wisdom, apply a contextual approach to Islamic law, and empower the community. Dayah scholars are also responsive to contemporary issues developing in society. The idea of Wasathiyah Islam promoted by Dayah scholars in Aceh is an effort to maintain balance in the practice and understanding of religion, while still keeping up with the times.